Youssef Ouaglissi’s, poem “The manifestations of a prophet fallen inadvertently from death”, a stylistic approach. - Derradji, Safia (Journal of Human Sciences, 2021)
In analyzing Youssef Ouaglissi’s poem “The manifestations of a prophet fallen inadvertently from death”, published in his collection entitled “Jaafar at-Tayar Alienation”, we followed a stylistic approach that consist of dissecting the text from the smallest to the largest semantic units, tracking any element that would make the distinction of the manifestations and the surprise of the receiver. We looked at the aesthetic connotations associated with the poet’s innovation in view to explain his style and deduce his philosophy of life. This poem deals with the black decade during which the country was scrambling between ruin and resistance. Youssef Ouaglissi’s poem was an image of a dream, of the slaughtered homeland, of the wounds. It was a speech on alienation and identity alike.